Competing with asking prices. Issue 2 (May 2017) - Lester, Benjamin; Visschers, Ludo; Wolthoff, Ronald
Abstract : In many markets, sellers advertise their good with an asking price . This is a price at which the seller will take his good off the market and trade immediately, though it is understood that a buyer can submit an offer below the asking price and that this offer may be accepted if the seller receives no better offers. We construct an environment with a few simple, realistic ingredients and demonstrate that, by using an asking price, sellers both maximize their revenue and implement the efficient outcome in equilibrium. We provide a complete characterization of this equilibrium and use it to explore the implications of this pricing mechanism for transaction prices and allocations.